Sea level: measuring the bounding surfaces of the ocean - Tamisiea, M.E.; Hughes, C.W.; Williams, S.D.P.; Bingley, R.M. (Royal Society, 2014)
The practical need to understand sea level along the coasts, such as for safe navigation given the spatially variable tides, has resulted in tide gauge observations having the distinction of being some of the longest instrumental ocean records. Archives of these records, along with geological constraints, have allowed us to identify the century-scale rise in global sea level. Additional data sources, particularly satellite altimetry missions, have helped us to better identify the rates and causes of sea level rise and the mechanisms leading to spatial variability in the observed rates. Analysis of all of the data reveals the need for long-term and stable observation systems to assess accurately the regional changes as well as to improve our ability to estimate future changes in sea level. While information from many scientific disciplines is needed to understand sea level change, this paper focuses on contributions from geodesy and the role of the ocean’s bounding surfaces: the sea surface and the Earth’s crust.